﻿A comparative study of combination treatments in metastatic 4t1 cells: everolimus and 5- fluorouracil versus lithium chloride and 5-fluorouracil - Dhiya Altememy; Pooria Mohammadi Arvejeh; Fatemeh Amini Chermahini; Akram Alizadeh; Madineh Mazarei; Pegah Khosravian (Pensoft Publishers, 2022)
Background: Combination therapy has been one of the most pioneering and strategic approaches implemented for malignancy treatment, which can intentionally influence multiple signaling pathways involved in cancer growth and progression. In the present study, the effects of 5-fluorouracil (5FU) in combination with everolimus (EVE) or lithium chloride (LiCl) were evaluated in 4T1 metastatic breast cancer cells and compared to control and each other. Methods and results: The resazurin assay, CompuSyn, flow cytometry, and real-time PCR were used to investigate cell proliferation, drug synergism, apoptosis, and gene expression. In comparison to the ternary combination of the drugs, the findings showed that cytotoxicity (p-value < 0.0001) and apoptosis (p-value < 0.0001) of two-by-two combinations increased dramatically as a consequence of the extreme synergy between 5FU and EVE or LiCl. Moreover, the hypoxiainducible transcription factor 1-alpha (HIF-1α) and the vascular endothelial growth factor (VEGF) downregulated considerably compared to control (p-value < 0.0001) by combination therapies of EVE-5FU and 5FU-LiCl; however, only VEGF displayed significant downregulation in comparison to single therapies. Conclusion: The findings showed that the combination of 5FU-LiCl increased cell cytotoxicity and apoptosis significantly more than EVE-5FU but suggests a clinical potential for both to treat metastatic breast cancer encouraging validation of these results in pre-clinical models.